Central Dopaminergic System and Its Implications in Stress-Mediated Neurological Disorders and Gastric Ulcers: Short Review - Naila Rasheed; Abdullah Alghasham (Hindawi Limited, 2012)
For decades, it has been suggested that dysfunction of dopaminergic pathways and their associated modulations in dopamine levels play a major role in the pathogenesis of neurological disorders. Dopaminergic system is involved in the stress response, and the neural mechanisms involved in stress are important for current research, but the recent and past data on the stress response by dopaminergic system have received little attention. Therefore, we have discussed these data on the stress response and propose a role for dopamine in coping with stress. In addition, we have also discussed gastric stress ulcers and their correlation with dopaminergic system. Furthermore, we have also highlighted some of the glucocorticoids and dopamine-mediated neurological disorders. Our literature survey suggests that dopaminergic system has received little attention in both clinical and preclinical research on stress, but the current research on this issue will surely identify a better understanding of stressful events and will give better ideas for further efficient antistress treatments.